Food security and socio-economic characteristics of farming families in Coto Brus, Costa Rica - Rodríguez González, Shirley (2019)
The objective of this article was to analyze food security of farming families in the minicipality of Coto Brus and its relationship with their socioeconomic characteristics. Data was collected in 2015 from 34 families, applying three techniques: structured interview, semi-structured interview, and participatory observation. The families’ socio-economic characteristics related to property, management, and family work were determined, as well as the families’ perception of their food security. Data was analyzed with the SPSS program. The average size of properties is 6.5 hectares. Production management is shared, where crops more related to the market are in charge of men, while food production for self-consumption is mainly done by women. The technology used in the production is manual labor. A total of 67% of the families experienced food insecurity. Those families with food security presented the following characteristics: greater property size, higher monthly income, and income from agricultural work on their farm. It is concluded that food security of the families is related to the size of the property, which defines their income and their access to healthy and safe food.